Mortality and immunovirological outcomes in patients with advanced HIV disease on their first antiretroviral treatment: differential impact of antiretroviral regimens. (29th October 2022) - Burgos, Joaquin; Moreno-Fornés, Sergio; Reyes-Urueña, Juliana; Bruguera, Andreu; Martín-Iguacel, Raquel; Raventos, Berta; Llibre, Josep M; Imaz, Arkaitz; Peraire, Joaquim; Orti, Amat-Joaquim; Dalmau, David; Casabona, Jordi; et al.
Abstract: Objectives: To assess the clinical and immunovirological outcomes among naive patients with advanced HIV presentation starting an antiretroviral regimen in real-life settings. Methods: This was a multicentre, prospective cohort study. We included all treatment-naive adults with advanced HIV disease (CD4+ T cell count < 200 cells/mm 3 or presence of an AIDS-defining illness) who started therapy between 2010 and 2020. The main outcomes were mortality, virological effectiveness (percentage of patients with viral load of ≤50 copies/mL) and immune restoration (percentage of patients with CD4+ T cell count above 350 cells/mm 3 ). Competing risk analysis and Cox proportional models were performed. A propensity score-matching procedure was applied to assess the impact of the antiretroviral regimen. Results: We included 1594 patients with advanced HIV disease [median CD4+T cell count of 81 cells/mm 3 and 371 (23.3%) with AIDS-defining illness] and with a median follow-up of 4.44 years. The most common ART used was an integrase strand transfer inhibitor (InSTI) regimen (46.9%), followed by PI (35.7%) and NNRTI (17.4%), with adjusted mortality rates at 3 years of 3.1% (95% CI 1.8%–4.3%), 4.7% (95% CI 2.2%–7.1%) and 7.6% (95% CI 5.4%–9.7%) ( P  = 0.001), respectively. Factors associated with increased mortality included older age and history of injection drug use, whilst treatment with an InSTI regimen was a protective factor [HR 0.5 (95% CI 0.3–0.9)]. A sensitivity analysis with propensity score procedure confirms these results. Patients who started an InSTI achieved viral suppression and CD4+ T cell count above 350 cells/mm 3 significantly earlier. Conclusions: In this large real-life prospective cohort study, a significant lower mortality, earlier viral suppression and earlier immune reconstitution were observed among patients with advanced HIV disease treated with InSTIs.